2013
DOI: 10.1155/2013/704947
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activity of Propolis-Containing Toothpaste on Oral Health Environment in Patients Who Underwent Implant-Supported Prosthodontic Rehabilitation

Abstract: The soft and periodontal tissues surrounding dental implants are particularly susceptible to bacteria invasion and inflammatory reactions due to complex histological structures. This study was carried out to investigate the influence of a propolis-containing hygienic agent on selected oral health parameters, oral microflora, and the condition of periodontal health. Sixteen subjects who underwent an oral rehabilitation with dental implants were selected and randomly assigned into two groups, which received a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
5
40
0
1
Order By: Relevance
“…The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations. For implant-borne restorations, the professional maintenance CPGs were sub-divided for removable and fixed restorations and further divided into biological maintenance and mechanical maintenance for each type of restoration.…”
Section: Resultsmentioning
confidence: 99%
“…The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations. For implant-borne restorations, the professional maintenance CPGs were sub-divided for removable and fixed restorations and further divided into biological maintenance and mechanical maintenance for each type of restoration.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the dentifrice with 0.3% triclosan/copolymer was significantly more effective than a dentifrice without triclosan in improving peri‐implant outcomes in patients with peri‐implant mucositis. In another RCT on 16 patients with various types of implant restorations, Morawiec et al compared the use of a dentifrice containing ethanol extract of Brazilian green propolis with a placebo dentifrice without the propolis on selected oral health parameters, oral microflora, and periodontal health. The authors showed that over an 8‐week period, the use of propolis ‐containing dentifrice seemed to have a beneficial effect on peri‐implant tissues and plaque accumulation, resulting in improved scores in approximal plaque index, oral hygiene index‐debris component, and bleeding on probing.…”
Section: Resultsmentioning
confidence: 99%
“…Each type of restoration/prosthesis requires careful planning, meticulous coordination of care, and a long‐term partnership with the patient to maintain an enduring result. This includes an appropriate patient recall regimen and professional as well as at‐home maintenance . The fabrication of implant restorations also represents a considerable investment of time and resources, with the anticipation of an enduring result by patients and clinicians.…”
mentioning
confidence: 99%
“…Therefore, a set of CPGs was created for each type of restoration comprising (1) patient recall, (2) professional maintenance, and (3) at‐home maintenance. The CPGs are presented in Table for tooth‐borne restorations and Table for implant‐borne restorations . For tooth‐borne restorations, the professional maintenance and at‐home maintenance CPGs were subdivided for removable and fixed restorations.…”
Section: Resultsmentioning
confidence: 99%